The role of the university in the field of nanotechnology : the case of the University of the Witwatersrand. - Iyuke, Patience Odiri (My University, 2008)
This study examines the role of the university in the domain of nanotechnology research and training using the University of the Witwatersrand (Wits) as a case study. It focused on the Faculties of Science and Engineering, given their involvement in the field. It is essentially a qualitative study based on documentary analysis and semi-structured interviews with academic staff members. It shows how the University of Witwatersrand has responded to the South African National Nanotechnology Strategy set by the South African government to enhance the country’s global competitiveness and sustainable economic growth in strategic areas. The study reveals that Wits has selectively by firmly engaged in the domain of nanotechnology and has laid the foundations for a comprehensive programme in both research and training. However, its success in this direction will largely depend upon the ways it maximises the use of the increasing opportunities offered by globalization and it manages the constraints associated with it. By opportunities here I refer to the multiplicity of research sites outside the narrow academic domain and the increasing interest displayed by government, the private sector and relevant international agencies in the field. The constraints are connected to the fact that the field of nanotechnology remains incipient and suffers from the uncertainties surrounding a relatively young field of enquiry in universities in South Africa (financial shortages, lack of skills etc).
Keywords: Nanotechnology; Globalisation; Knowledge Production; University; Policy; National Strategy; Experience